2016
DOI: 10.1080/01419870.2016.1260751
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Semitism and opposition to Israeli government policies: the roles of prejudice and information

Abstract: Past research on the link between anti-Semitism and criticism of the Israeli government has revealed a partial correlation between the two. However, among the political arguments that have inspired such research, one has gone unaddressed: that criticism of the Israeli government along with silence about more egregious human rights abuses committed elsewhere can only arise from anti-Semitism. This article investigates the link between knowledge of conflicts around the world, anti-Semitism, Islamophobia, and cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Second, the mean antisemitism score for those with higher levels of antisemitism but lower anti-Israel attitudes (AS index 3.49 SD .46) is indeed lower than that for those critical of both Israel and Jews (3.81 SD .70). This indicates, following Kaplan and Small (2006), Beattie (2017) and Staetsky (2017), that attitudes extremely critical of Israel may indeed provide one pathway toward antisemitism, especially (but not only) for Muslim students (we lack the data to test for the presence of antisemitism among far right or far left students as highlighted in Staetsky's analysis of his much larger sample). Finally, the fact that our sample also includes Republican students with antisemitic attitudes who are largely supportive of Israel suggests that the diffusion of antisemitic views runs not only through "Israel."…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Second, the mean antisemitism score for those with higher levels of antisemitism but lower anti-Israel attitudes (AS index 3.49 SD .46) is indeed lower than that for those critical of both Israel and Jews (3.81 SD .70). This indicates, following Kaplan and Small (2006), Beattie (2017) and Staetsky (2017), that attitudes extremely critical of Israel may indeed provide one pathway toward antisemitism, especially (but not only) for Muslim students (we lack the data to test for the presence of antisemitism among far right or far left students as highlighted in Staetsky's analysis of his much larger sample). Finally, the fact that our sample also includes Republican students with antisemitic attitudes who are largely supportive of Israel suggests that the diffusion of antisemitic views runs not only through "Israel."…”
Section: Discussionmentioning
confidence: 86%
“…Recent survey research documenting the overlap between attitudes toward Jews and Israel has found a statistically positive relationship between antisemitism and anti-Israel sentiments. Beattie (2017), based on a convenience sample using Mechanical Turk, reported a statistically significant correlation (r = .27) between anti-Israel attitudes and antisemitism. Based on a cross-national European sample, and using a truncated version of the ADL's antisemitism scale, Kaplan and Small (2006) found that anti-Israel attitudes were highly predictive of antisemitism, yet this result varied significantly across countries, and Muslim respondents critical of Israel were much more likely to hold antisemitic views than other respondents.…”
Section: Theoretical Background and Empirical Expectationsmentioning
confidence: 96%
“…A second set of studies focuses on particular ideological or religious contexts, including rightwing, left-wing, and Islamic variants of antisemitism (Kahmann 2017;Wodak 2018;Herf 2007;Hirsh 2018;Jikeli 2015a;Wetzel 2013;Webman 2010). A third strand of research has analyzed the prevalence and determinants of antisemitic attitudes (Beattie 2017;Bilewicz et al 2013;F. Cohen et al 2009;Kaplan and Small 2006;Staetsky 2017Staetsky , 2019bBrym 2019), while a fourth line on inquiry has sought to explain variation in the occurrence of antisemitic incidents (Smith 2008;Jacobs et al 2011;Feinberg 2020).…”
Section: Definition Past Research and The Utility Of A Threedimensional Frameworkmentioning
confidence: 99%
“…In contrast to these positive trends among Christians, some have argued that there is a new antisemitism, which links criticism of Israel to negative attitudes toward Jews. Several studies find this anti-Israel-anti-Jewish connection most strongly among Muslims around the world (Baum and Nakazawa 2007;Beattie 2017;Cohen et al 2011;Dinnerstein 2004;Gerstenfeld 2007;Jaspal 2014;Kaplan and Small 2006;Kempf 2012Kempf , 2015Klug 2003Klug , 2013Tausch 2014). But there is little research on such a correlation among American Muslims.…”
Section: Religionmentioning
confidence: 99%